Channel Conflict and Coordination in the E‐Commerce Age - Tsay, Andy A.; Agrawal, Narendra (Production and Operations Management, 2004)
A number of factors, including developments in Internet‐based commerce and third‐party logistics, have led many companies to consider engaging in direct sales. Such a company may at once be both a supplier to and a direct competitor of any existing reseller partners (e.g., land‐based retailers), which can result in “channel conflict.” This can have momentous implications for distribution strategy. To generate managerial insights into this important issue, we develop a model that captures key attributes of such a setting, including various sources of inefficiency. We examine these in detail and identify a number of counterintuitive structural properties. For instance, the addition of a direct channel alongside a reseller channel is not necessarily detrimental to the reseller, given the associated adjustment in the manufacturer's pricing. In fact, both parties can benefit. Finally, we examine ways to adjust the manufacturer‐reseller relationship that have been observed in industry. These include changes in wholesale pricing, paying the reseller a commission for diverting customers toward the direct channel, or conceding the demand fulfillment function entirely to the reseller. The latter two schemes could be mutually beneficial in that they achieve a division of labor according to each channel's competitive advantage.